Multilayers fast mode decision algoritham for scalable video coding over IEEE 802.11G wireless LAN - Maarif, Haris al-Qodri (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Scalable Video Coding (SVC) is the extension of H.264/AVC where the features are developed from the H.264/AVC, so that SVC has more complex features for the video coding standard. This provides higher coding complexity in SVC encoder which causes higher encoding time for SVC. SVC is gaining great interest because of its ability and scalability to adapt in various network conditions. SVC allows partial transmission and decoding of a bitstream. This research deals with fast mode decision algorithm for decreasing encoding time or fastening the mode decision process of the SVC encoder. Moreover, the performance of SVC over wireless network has been evaluated. The simulation tools can be of great help for a better understanding of the streaming analysis over the network. Hence, this research utilizes Scalable Video Evaluation Framework (SVEF). The fast mode decision scheme has been implemented and successfully decreased encoding time with negligible loss of quality and bitrate requirement. The streaming simulation has also been performed using the SVEF simulator. The simulation result shows the proposed fast mode decision algorithm provides time saving up to 45 % while maintaining video quality with negligible PSNR loss. For the streaming video, the received packets on the receiver can be reconstructed on maintained video quality with also negligible PSNR loss.